Bad news Bears - Linklater, Richard, 1960-; Thornton, Billy Bob.; Kinnear, Greg, 1963-; Harden, Marcia Gay.; Stoffers, Rogier; Shearmur, Edward; Lancaster, Bill, 1947-1997.; Paramount Pictures Corporation (Hollywood, CA : Paramount Pictures, 1976)
Morris Buttermaker, former--very briefly--a professional baseball player turned exterminator, is recruited to coach and train a failing Little League team. Having lost every game they have ever played, the kids challenge the coach to help them change their losing ways before the season is over.
Based upon the film written by Bill Lancaster.
Special features: Director's commentary; deleted scenes & hilarious outtakes; featurettes; video baseball cards.
Director of photography, Rogier Stoffers ; editor, Sandra Adair ; original music, Edward Shearmur ; costume designer, Karen Patch ; production designer, Bruce Curtis.
Billy Bob Thornton, Greg Kinnear, Marcia Gay Harden.
MPAA rating: PG-13; for rude behavior, language throughout, some sexuality and thematic elements.
DVD, region 1, widescreen presentation; Dolby Digital.
Keywords: Little League baseball -- Drama; Baseball coaches -- Drama; Baseball players -- United States -- Drama; Feature films; Video recordings for the hearing impaired; Sports -- Feature